Postgraduate students' use of reporting verbs in literature review writings - Lee, Geok Imm; Tan, Helen (Penerbit Universiti Kebangsaan Malaysia, 2023)
Academic writing is intrinsically a persuasive discourse and for the argument to be well received by the discourse community, citation is mandatory. A successful integral citation requires writers to use appropriate reporting verbs in their writing texts which is different from non-integral citation. However, past studies have shown that novice writers had difficulties using reporting verbs in integral citations. Therefore, this action research sought to investigate the frequencies and forms of reporting verbs used by novice postgraduate students in their literature review writings. Using convenience sampling and Hyland’s (2002) Categories of Reporting Verbs, a total of 32 literature review writings of non-native novice postgraduate students were analysed quantitatively and qualitatively. The findings illustrated that although the students used all the three categories of reporting verbs, Research Acts reporting verbs were more dominantly used, followed by Discourse Acts reporting verbs. The least used was Cognition Acts reporting verbs. As for the forms used, the most common forms under Research Acts were found and conducted while stated, concluded and suggested were the most dominant forms under Discourse Acts. As for Cognition Acts, believed and agreed were the key forms. To conclude, the study demonstrated the need to raise the novice writers’ awareness on the three different categories of reporting verbs that could be used in integral citations for a more effective academic writing.